Tata Kelola Pemerintahan melalui Aplikasi SUPER RT di Kelurahan Loktuan Kota Bontang - Nayunda Nur Aini Ramadhani (Journal Social Politica, 2020)
The purpose of this study is to describe and analyze governance carried out by the Loktuan Village Government, Bontang CIty through the SUPER RT Application for services to the community. Data collection techniques in this study were obtained by observing, interviewing and documents that have been processed by the researcher using qualitative research methods. Informants who have been determined are the parties who have a direct role in the implementation of this application. The results showed that governance that is carried out through the SUPER RT application in Loktuan village, Bontang City has met the requirements of good governance. The existence of services through the SUPER RT application makes it easy for Community Leader to provide services to the community. Service becomes easy, fast, saves time and effort. However, governance through this application still has many shortcomings, for example; 1) frequent interruptions to the latest android version, 2) awareness of using the application towards elderly Community Leaders, 3) availability of android or ios gadgets. This application goes through the planning to evaluation stages in 2017.